ANALYSIS OF SOCIO-PHILOSOPHICAL IDEAS IN THE WORKS OF ALISHER NAVOI - Karimov Muhammadrakhim Salimjon son; Rozimatov Umidjon (American Journals Publishing, 2024)
Present article offers a philosophical examination of the manifold aspects of Alishir Navai’s creative life. Also, it discusses the contemporary relevancy of the notions of justice, humanity which are found frequently in Navai’s works. Navai’s works are filled with philosophical speculations about the interrelation of an individual and the society, the earthly happiness, man and the community, and thoughts on education and enlightenment.
Keywords: Morals, justice, humanity, spirituality, reason, idea, tasavvuf, being.